METODE PENANGGULANGAN EROSI SUNGAI MENGGUNAKAN TEKNOLOGI REHABILITASI BANGUNAN PELINDUNG TEBING - Zais, Syamsul (Universitas Majalengka, 2019)
Hilly areas where the slope of the slope is very sharp, ie more than 30 ° very often occur cliff collapse. As a result of the collapse of this cliff will cause siltation of the river by soil material, rocks and trees. When large rainfall and high intensity of the valley will be filled with water, while the flow of water that flows is relatively small. This is caused by a pile of collapsed material in the river that functions as a water flow. landslides often occur on the cimanuk river bank caused by rising water discharge in the Cimanuk river which have a direct impact on the area of ​​agricultural land in the village Karang Karang to overcome the problem of floods, landslides and erosion that occur in the cimanuk river Karangsambung village that is with the rehabilitation project of the river bank protective wall using method of spun pile foundation and gabion. The Spun Pile used must have D'0.40 each with a length of 10m. 12m, and 14m to match the conditions in the field and there are 6 blocks that will be installed spun pile foundation and gabion, each block has been calculated according to its elevation. casting is carried out with K225 concrete. The gabion material used has a size of 2.5x 1.5x 0.5 gabion that has been installed will be coated with geotextile mat. on the front tongue of the gabion with a total volume calculation of 150m Determine the diameter of the 40cm stake using the Qijin formula